Pengaruh Edukasi Kesehatan Reproduksi Pada Remaja Putri Terhadap Personal Hygiene Saat Menstruasi - Diyana Faricha Hanum; Dwi Faqihatus Syarifah Has; Munisah Munisah (IJMT : Indonesian Journal of Midwifery Today, 2022)
Adolescent girls are more at risk of being infected with their reproductive organs, this event occurs because of a lack of attitude in maintaining personal hygiene, especially when menstruating. The purpose of this study was to determine the effect of reproductive health education on adolescent girls on personal hygiene during menstruation in the Midwifery Study Program, Faculty of Health, University of Muhamadiyah Gresik. This research is analytic observational, the sample used is 20 respondents, the sample is taken using random sampling. Collecting data using an instrument in the form of a questionnaire. Statistical test using univariate and bivariate analysis with T test. The results of the paired samples t-test showed that there was a significant difference sig (2-tailed=0.000) between pre-test and post-test data from the effect of reproductive health education on adolescents on personal hygiene during menstruation. The conclusion is that there is a significant effect on respondents after being given reproductive health education to adolescent girls on personal hygiene during menstruation.